Pemberdayaan Masyarakat Melalui Edukasi Gizi: Strategi Pencegahan Stunting di Kabupaten Seluma - Yuliantini, Emy; Kamsiah, Kamsiah; Eliana, Eliana; Wijaya, Andra Saferi; Yunita, Yunita (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The prevalence of stunting in Indonesia will decrease from 24.4% to 21.6% in 2022. In 2022, Seluma Regency will be 22.1% and in Bengkulu Province, 32.8%. The aim of this community service is to empower the community with nutrition education, prevention, and early detection of stunting in Seluma district. This community service is carried out using mentoring methods, lectures, and assessments from pre- and post-tests to determine the increase in knowledge and skills of mothers of toddlers. There is an increase in the knowledge and skills of mothers of toddlers, cadres, and village officials regarding prevention, early detection, and the benefits of the stunting reduction and prevention strategy program in Seluma Regency. There is increasing community independence regarding prevention, early detection, the benefits of the Reduction Strategy Program, and the hope that village cadres and officials can apply the knowledge and skills that have been obtained during activities to provide education and assistance to every community in their area.